Sams teach yourself SQL in 24 hours - Stephens, Ryan (Indianapolis, Indiana : Peasrons Education, 2016)
In just 24 lessons of one hour or less, Sams Teach Yourself SQL in 24 Hours, Sixth Edition, helps you use SQL to build effective databases, efficiently retrieve data, and manage everything from performance to security. This book&;s straightforward, step-by-step approach shows you how to work with database structures, objects, queries, tables, and more. In just hours, you will be applying advanced techniques, including views, transactions, web connections, and powerful Oracle and SQL Server extensions. Every lesson builds on what you&;ve already learned, giving you a rock-solid foundation for real-world success. Step-by-step instructions carefully walk you through the most common SQL tasks. Practical, hands-on examples show you how to apply what you learn. Quizzes and exercises help you test your knowledge and stretch your skills. Notes and tips point out shortcuts and solutions.